Reframing decision making in education : democratic empowerment of teachers and parents - Rettig, Perry Richard (Rowman & Littlefield, 2016)
Reframing Decision Making in Education begins by describing the current status of American schools and concludes with a description of the organizational structure, leadership, and decision making practices necessary to make our schools operate in a manner congruent with those democratic principles we espouse as a country.